Influência da adição de elementos de liga na microestrutura de superligas Ni-15%Nb-xAl-yTi - Arruda, Matheus Stolf Toledo (2023)
Controlling the fraction of precipitates and their morphology are important parameters in precipitation-hardenable superalloys, since precipitates provide increased mechanical properties in these alloys that are exposed to severe conditions of temperature and mechanical strength. Ni Nb superalloys with additions of Ti and Al were produced in concentrations of Ni15Nb2Al2Ti, Ni15Nb2Al4Ti and Ni15Nb4Al1Ti and obtained polycrystalline alloys composed of a matrix of Ni (γ), an irregular phase of Ni3Nb (γ’’) and precipitates of the Gamma Prime phase (γ ') composed by γ' Ni3(Al,Ti). Solubilization and aging thermal treatments were carried out to obtain greater volume and control of the morphology of the precipitated phases. Optical microscopy (OM), scanning electron microscopy (SEM), electron emission spectroscopy (EDS) and X-ray diffraction (XRD) analyzes were performed on the samples to evaluate the microstructures, the chemical composition of the phases and crystalline structures . Vickers microhardness tests were carried out to observe the effects of heat treatments on the material's hardness properties. Thus, it was possible to observe the influence of Nb together with the effects of adding Al and Ti on the microstructures and hardness of Ni superalloys. Due to additions of Ti and Al other phases may form precipitates. By varying the concentrations of Ti and Al in the samples, different Ti/Al ratios were obtained and thus it was possible to analyze their effects on the microstructure and hardness property. The increase in the Ti/Al ratio led to a greater formation of the Ni3Ti phase. Increasing the amount of Ti + Al increased the microhardness values of the Ni15Nb2Al4Ti alloy (469 HV in the aged condition), followed by the Ni15Nb4Al1Ti alloy (422 HV in the aged condition) and finally the Ni15Nb2Al2Ti alloy (395 HV in aged condition).